Microstructure and properties of polymeric composite materials based on polyethylene and thermally extended graphite for transport systems - Lysenkov, E. A.; Klymenko, L. P. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2021)
The effect of thermoexpanded graphite (TEG) on the microstructure and functional properties of polymer composites based on high-density polyethylene (HDPE) has been studied by optical microscopy, differential scanning calorimetry and mechanical analysis. There has been proven the efficiency of the method of mixing polymer composites using a piston extruder, which provides a more uniform distribution of the filler in the polymer matrix. It is shown that the introduction of TEG leads to a decrease in the degree of crystallinity and melting point of systems based on high-density polyethylene, which is a consequence of the destruction or increase in the defect of the crystal structure of the polymer matrix under the influence of TEG. With the introduction of 1 % of TEG, the melting point decreased from 415.0 to 408.5 K. With the introduction of 3 % of TEG, the thermal conductivity increased from 0.18 W/(m·K) (for HDPE) to 0.76 W/(m·K). The extreme change in the thermal conductivity of polymer composites is a consequence of the formation of TEG in the polymer matrix of the percolation cluster, the mesh of the filler, which penetrates the entire volume of the material. As a result of the conductivity studies, the percolation threshold of thermal conductivity has been determined for these HDPE-TEG systems, which is 0.6 %. Microscopic studies confirmed the formation of the percolation cluster obtained by thermal conductivity. It is shown that at the content of 0.6 % of TEG, there is formed a continuous cluster. The formation of this cluster is confirmed by mechanical studies. An increase in mechanical strength has been recorded, which increases from 30.5 MPa (for HDPE) to 42.8 MPa at 5 % filler content, and this is promising for the use of these materials in transport systems.